Analyzing Health Disparities through Epidemiological Data: A Conceptual Framework for Evidence-Based Solutions - Leesi Saturday Komi,; Ashiata Yetunde Mustapha,; Adelaide Yeboah Forkuo,; Damilola Osamika, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Health disparities persist as a significant global challenge, with unequal health outcomes rooted in social, economic, and structural factors. This paper analyzes these disparities through a conceptual framework informed by epidemiological data, emphasizing the role of evidence-based strategies in addressing inequities. Key insights from epidemiological research highlight disparities across race, gender, socioeconomic status, and geography, underscoring the need for targeted interventions and systemic reforms. Evidence-based solutions are proposed, including public health programs, community engagement, and policy changes addressing social determinants of health. Challenges such as resource constraints and resistance to systemic change are acknowledged alongside technological innovations and multi-sectoral collaboration opportunities. This study concludes by advocating for coordinated efforts among policymakers, researchers, and healthcare practitioners to ensure equitable health outcomes for all populations, emphasizing the critical role of data in shaping effective and sustainable solutions.
Keywords: Health disparities; Epidemiological data; Social determinants of health; Evidence-based solutions; Health equity; Policy reform